Subregional DXA-derived vertebral bone mineral measures are stronger predictors of failure load in specimens with lower areal bone mineral density, compared to those with higher areal bone mineral density - Briggs, Andrew; Perilli, E.; Codrington, J.; Reynolds, K.; Parkinson, I.; Wark, J. (Springer-Verlag, 2014)
Measurement of areal bone mineral density (aBMD) in intravertebral subregions may increase the diagnostic sensitivity of dual-energy X-ray absorptiometry (DXA)-derived parameters for vertebral fragility. This study investigated whether DXA-derived bone parameters in vertebral subregions were better predictors of vertebral bone strength in specimens with low aBMD, compared to those with higher aBMD. Twenty-five lumbar vertebrae (15 embalmed and 10 fresh-frozen) were scanned with posteroanterior- (PA) and lateral-projection DXA, and then mechanically tested in compression to ultimate failure. Whole-vertebral aBMD and bone mineral content (BMC) were measured from the PA- and lateral-projection scans and within 6 intravertebral subregions. Multivariate regression was used to predict ultimate failure load by BMC, adjusted for vertebral size and specimen fixation status across the whole specimen set, and when subgrouped into specimens with low aBMD and high aBMD. Adjusted BMC explained a substantial proportion of variance in ultimate vertebral load, when measured over the whole vertebral area in lateral projection (adjusted R2 0.84) and across the six subregions (ROIs 2–7) (adjusted R2 range 0.58–0.78). The association between adjusted BMC, either measured subregionally or across the whole vertebral area, and vertebral failure load, was increased for the subgroup of specimens with identified ‘low aBMD’, compared to those with ‘high aBMD’, particularly in the anterior subregion where the adjusted R2 differed by 0.44. The relative contribution of BMC measured in vertebral subregions to ultimate failure load is greater among specimens with lower aBMD, compared to those with higher aBMD, particularly in the anterior subregion of the vertebral body.